Taxonomic review, morphometry, and phylogenetic analysis of Mahanarva (Ipiranga) Fennah, 1968 (Hemiptera: Auchenorrhyncha: Cercopidae) - Jéssica Meneghetti; Alejandro Jose Biganzoli-Rangel; Gervásio Silva Carvalho; Andressa Paladini (Arthropod Systematics & Phylogeny)
Mahanarva (Ipiranga) Fennah, 1968, currently comprises nine described species. The subgenus is characterized by an inflated postclypeus with a convex profile, longer than wide tegmina, and male genitalia with a short, laterally compressed aedeagus with a pair of slender dorsal processes. In this study, a phylogenetic hypothesis based on morphological data is presented to test the monophyly of Mahanarva (Ipiranga) and infer the relationship between its species. We present the redescriptions of its species and the description of two new species, Mahanarva (Ipiranga) obliqua sp. nov. and Mahanarva (Ipiranga) nefasta sp. nov., along with a dichotomous key for identification. Moreover we synonymized M. (I.) vittata and M. (I.) fortunata based on morphological characters and a principal component analysis. The PCA results suggested no differences on the morphospace between these species; however, cluster analysis resulted in three groups. These groups don’t show a geographic pattern structure or stable genitalic morphological differences. For phylogenetic analyses, a data matrix with 30 taxa and 56 characters was constructed. Based on the results of phylogenetic analyses, Mahanarva (Ipiranga) is recovered as paraphyletic and grouped with Mahanarva (Mahanarva) + Kanaima.